Challenges in Educational Inclusion of Students with Autism Disorders in Primary Schools - Šilc, Mateja; Schmidt Krajnc, Majda (Revija za elementarno izobraževanje, 2022)
Students with autism disorders require various adaptations to the learning environment and specific learning strategies, which is a significant challenge for schools and teachers. The success of their inclusion depends primarily on the attitude, experience and competence of the school's professional staff, the availability of resources, and the possibility of teamwork. Nevertheless, research shows a lack of critical conditions for implementing inclusive education of these students, which is reflected in an increased risk of their academic and social exclusion and of increasing teachers' workload. Schools also lack flexibility in working with parents. The solution lies in ging beyond the ideals of educational inclusion, respecting equity, and accomplishing the social model of disability treatment.